Rencana Strategis PT. Inovasi Digital Nusantara (IDN) - Jusmawati Jusmawati; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Strategic planning is an important component in organizational management to achieve long-term goals effectively and efficiently. This study discusses the implementation of strategic planning at PT. Inovasi Digital Nusantara (IDN), a digital innovation company that focuses on developing e-commerce applications in Southeast Asia. The study highlights the importance of change management, technology integration, and business environment evaluation in the formulation and implementation of corporate strategy. The strategic approaches used include Balanced Scorecard, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM) to improve company performance and competitiveness. The results of the study indicate that the implementation of data-based strategic planning and continuous evaluation allows PT. IDN to adapt to current market and technology changes, improve operational efficiency, and meet customer needs optimally. Recommendations are made for the company to continue to develop a culture of innovation and consistently update its strategy in order to achieve the company's long-term vision.